A Web-Based Respiratory Pathogen Laboratory Report for Summarizing Key Metrics to Stakeholders. (21st September 2018) - Christensen, Paul; Long, S Wesley; Olsen, Randall; Davis, James; Musser, James
Abstract: Background: The Centers for Disease Control and Prevention (CDC) provides data regarding influenza activity. However, daily and weekly statistics summarizing regional hospital system observations are possibly most relevant for local decision making. Our microbiology laboratory implemented a daily web-based report to distribute respiratory pathogen data for our eight-hospital system to clinicians, hospital epidemiologists, infection control committees, system leadership, and the general public. Methods: Molecular and antigen laboratory result data from respiratory pathogen tests are extracted from our lab information system and subsequently inserted into a MySQL database. Using PHP: Hypertext Preprocessor, we analyzed the laboratory result data to produce a web-based report using the Chart.js framework. The four charts summarize the number of positive tests over time, the number of positive tests by patient location in our hospital system, the percent positive tests, and the number of each pathogen identified by our molecular test during a set time interval. We advertised the report at three separate committee meetings, where we also requested informal feedback. A link to the report was included in an email from the executive vice president of the hospital system. We monitored the visitor statistics, including Internet Protocol (IP) addresses. Results: We deployed the report to the cloud. Over 1 week, the report was accessed 932 times. Seventy percent of the originating IP addresses were from our hospital system, 10% were from other locations within the United States, 1% were from locations outside the United States, and 19% were from addresses that could not be mapped. Eighteen percent of the views were on mobile devices. The most common browser for desktop computers was Microsoft Internet Explorer (43% of all views). Visit count peaked at 241 views per hour right after the link was distributed by email. Thirty-six percent of all hour intervals saw no page views; excluding these, there were on average eight views per hour. Conclusions: In summary, we developed a web-based report that presents relevant statistics regarding respiratory pathogen testing in our laboratory. The report is updated daily to provide critical data to all stakeholders, including the general public. We developed the site with mobile devices in mind, which allows the charts and fonts to be readable on any platform. The charts are interactive, allowing the user to switch between daily and weekly reports using radio buttons. Data can be filtered by clicking the data labels in the chart legend. These features are possible because of our decision to develop a web-based report, as opposed to a Portable Document Format (PDF), spreadsheet, or word processing document. Anecdotal feedback collected at the time of rollout was universally positive. The report continues to be viewed daily.